2003
DOI: 10.1021/jo026555p
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Intramolecular Diels−Alder Reactions of Furo[3,4-c]pyridines in the Synthesis of Conformationally Restricted Analogues of Nicotine and Anabasine

Abstract: En route to conformationally restricted analogues of nicotine and anabasine, a novel synthetic route to bridged anabasines is described that hinges on a domino intramolecular [4 + 2]-cycloaddition/ring opening-elimination sequence of 3-amino-substituted furo[3,4-c]pyridines. Extension of this route to bridged nicotines, however, proved abortive, even when the dienophile tether is activated by a p-tolylsulfonyl group or when the diene moiety is activated by an electron-releasing methoxy substituent. A detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In contrast, heteroanalogues of isobenzofurans have received much less attention, although this situation is rapidly changing in recent years. , The heteroaromatic isobenzofurans reported to date include furo[3,4- b ]furans, thieno[2,3- c ]furans, furo[3,4- d ]oxazoles, furo[3,4- d ]isooxazoles, furo[3,4- d ]thiazoles, furo[3,4- b ]benzofurans, benzo[4,5]thieno[2,3- c ]furans, furo[3,4- b ]indoles, furo[3,4- b ]pyridines, furo[3,4- c ]pyridines, furo[3,4- d ]pyridazines, furo[3,4- d ]quinoxalines, and furo[3,4- c ]cinnolines . During the course of our studies on heteroisobenzofurans, we have recently reported the synthesis of a remarkably stable furo[3,4- c ]pyridine intermediate and established the unique advantages of intramolecular Diels−Alder reactions of furo[3,4- c ]pyridines in the synthesis of conformationally restricted analogues of nicotine and anabasine . The utility of heteroisobenzofurans as potential building blocks for the construction of polycyclic heteroaromatics is critically dependent on their availability as appropriate dienes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, heteroanalogues of isobenzofurans have received much less attention, although this situation is rapidly changing in recent years. , The heteroaromatic isobenzofurans reported to date include furo[3,4- b ]furans, thieno[2,3- c ]furans, furo[3,4- d ]oxazoles, furo[3,4- d ]isooxazoles, furo[3,4- d ]thiazoles, furo[3,4- b ]benzofurans, benzo[4,5]thieno[2,3- c ]furans, furo[3,4- b ]indoles, furo[3,4- b ]pyridines, furo[3,4- c ]pyridines, furo[3,4- d ]pyridazines, furo[3,4- d ]quinoxalines, and furo[3,4- c ]cinnolines . During the course of our studies on heteroisobenzofurans, we have recently reported the synthesis of a remarkably stable furo[3,4- c ]pyridine intermediate and established the unique advantages of intramolecular Diels−Alder reactions of furo[3,4- c ]pyridines in the synthesis of conformationally restricted analogues of nicotine and anabasine . The utility of heteroisobenzofurans as potential building blocks for the construction of polycyclic heteroaromatics is critically dependent on their availability as appropriate dienes.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of heteroisobenzofurans as potential building blocks for the construction of polycyclic heteroaromatics is critically dependent on their availability as appropriate dienes. The methods so far reported for the generation of furo[3,4- c ]pyridines include (i) thermal retro-Diels−Alder reactions of 1,4-epoxides, (ii) lithiation and subsequent o -silylation of pyridine-phthalides, and (iii) the Hamaguchi−Ibata reaction of o -aminodiazocarbonyl precursors. , As part of our continuing interest in the chemistry of azaisobenzofurans, we were particularly interested in the generation of thio-substituted furo[3,4- c ]pyridines by a Pummerer-based route and their applications in the synthesis of heterocyclic analogues of 1-arylnaphthalene lignans of biological significance.
1
2
3
…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic o-quinodimethanes and their stable analogs have been utilized in this regard [32][33][34][35][36]. On the other hand, the use of heteroaromatic isobenzofurans [37][38][39] as dienes is emerging as a powerful alternative to the above method. Furo [3,4-c]pyridine intermediate is one of the interesting member of the heteroaromatic isobenzofurans and important building block for the synthesis of isoquinoline derivatives such as heterocyclic analogues of 1-arylnaphthalene lignans [32].…”
Section: Introductionmentioning
confidence: 99%
“…Furo [3,4-c]pyridine intermediate is one of the interesting member of the heteroaromatic isobenzofurans and important building block for the synthesis of isoquinoline derivatives such as heterocyclic analogues of 1-arylnaphthalene lignans [32]. The generation of this intermediate include (i) thermal retro Diels-Alder reaction of 1,4-epoxides [40], (ii) lithiation and subsequent o-silylation of pyridine-phthalides [41], (iii) the Hamaguchi-Ibata reaction of oaminodiazocarbonyl precursors [33,39], and (iv) sequential Pummerer-Diels-Alder route [32]. Multicomponent coupling reactions offer an incredible level of diversity for the production of diverse structural entities from a few simple components.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this approach turned out to be inefficient in the case of constrained nicotines (cf. 4 , n = 1). , In this article we describe an alternative synthesis of both conformationally restricted ana-logues of nicotine and anabasine and their pharmacological activity for the α4β2 and α3β4 subtypes of the nicotinic receptor.…”
Section: Introductionmentioning
confidence: 99%